Ownership Risk in the Perspective of Islamic Law of Contract: Concept and Application on Modern Practices (Muhammadiyah University Press, 2018)
Daman Milkiyyah or ownership risk is an important element in Islamic Law of Contract as there are many implications arising from it. This concept also highlights one of the unique features of Islamic Law of Contract which promotes justice in transactions. The lack of a proper understanding of this concept may lead people to breaching Shariah principles as well as dealing with non-Shariah compliant transactions. It is the purpose of this paper to shed light on the fundamental concepts of ownership risk and its application on some of modern financial instruments. This work will write down the scattered though of ownership risk which has been discussed by Islamic classical scholars and continued by matching this concept to the existing modern financial instruments. In the end of the paper, we suggest further enhancement in the financial industry to adhere more towards shariah principle.